Rancang Bangun Sistem Informasi Marketplace Toko Bahan Kimia Berbasis Android - Sandi Pebriana; Purnomo Sidiq; Andriansyah Maulana (STMIK Banjarbaru, 2026)
This research designed and developed an Android-based marketplace information system specifically for chemical stores. The main problem addressed was the difficulty faced by consumers, including small-scale industry practitioners and academics, in obtaining chemical raw materials accompanied by technical specifications and material safety data sheets transparently. The methodology used was prototyping, which included operational requirement analysis, user interface design, and prototype implementation. The server-side development utilized an Application Programming Interface architecture to connect the database with the mobile application. The testing results showed that this application successfully facilitated secure chemical trading transactions, managed volume and mass-based inventory, and integrated product technical information into an easily accessible platform. The conclusion of this research stated that the implementation of a computerized marketplace effectively reduced transaction time and improved the standardization of raw material safety information for users.Keywords: Marketplace; Chemical Store; Android; Prototyping; Application Programming InterfaceAbstrakPenelitian ini telah merancang dan membangun sistem informasi marketplace khusus toko bahan kimia berbasis Android. Permasalahan utama yang diangkat adalah sulitnya konsumen, baik praktisi industri skala kecil maupun akademisi, dalam memperoleh bahan baku kimia yang dilengkapi dengan spesifikasi teknis dan panduan keselamatan bahan secara transparan. Pendekatan metodologi yang digunakan adalah prototyping, yang mencakup tahapan analisis kebutuhan operasional, perancangan antarmuka pengguna, dan implementasi purwarupa. Pengembangan sisi peladen memanfaatkan arsitektur Application Programming Interface untuk menghubungkan basis data dengan aplikasi seluler. Hasil pengujian menunjukkan bahwa aplikasi ini berhasil memfasilitasi transaksi jual beli bahan kimia secara aman, mengelola inventori berbasis spesifikasi volume dan massa, serta mengintegrasikan informasi teknis produk ke dalam satu platform. Kesimpulan dari penelitian ini menyatakan bahwa penerapan marketplace terkomputasi secara efektif mampu memangkas waktu transaksi dan meningkatkan standardisasi keamanan informasi bahan baku bagi para pengguna.